Curriculum as an instrument in developing leadership in modern school practice - Andersone, Rudite (Vodenje v vzgoji in izobraževanju, 2014)
The article addresses one of the objectives of the curriculum development - the assurance of leadership in the teaching/learning process in classrooms that is influenced by new technologies entering both our national economy and school practice, and by changes in the perception and the way of thinking of the young generation. The views of future teachers that were studied show that educational leadership for qualitative teaching/learning is described by the following principles: acknowledging the learners' experience and learning practices; preparing the learners for life in its broadest sense; recognizing non-formal learning combined with the formal one; promoting the learners' independent and autonomous learning; estimating the learners' needs in compliance with their learning activities and learning achievements; planning the activities and managing assistance to encourage learning.
Keywords: curriculum; education; kurikulum; leadership; modern school; new generations; ravnatelji; učitelji; vodenje